Etnis Bali di Lombok Barat (1942-2002) - Muhamad Sopyan; Andi Ima Kesuma; Jumadi Sahabuddin (Yupa: Historical Studies Journal, 2017)
This paper uses a qualitative approach design history that includes Groove heuristics, critique, interpretation and historiography. This paper describes a pattern of ethnic life Sasak Ethnic Balinese. The second encounter was part of the ethnic dynamics of patterns of social life, art and culture of the community of West Lombok, Bali, colonial empire domination Netherlands and Japan as well as the aftermath of independence. West Lombok in the course of its history has its own and unique patterns by showing the existence of the ideal cooperation between different ethnic religion in building a harmonious unity.